Influence of dimple shape on tribofilm formation and tribological properties of textured surfaces under full and starved lubrication. (August 2019) - Xu, Yufu; Zheng, Quan; Abuflaha, Rasha; Olson, Dustin; Furlong, Octavio; You, Tao; Zhang, Qiangqiang; Hu, Xianguo; Tysoe, Wilfred T.
Abstract: Lubrication conditions have significant influences on the formation of tribofilms and then affect tribological behavior. In this work, the influence of tribofilm formation on the tribological behavior of textured surfaces with oval shapes was measured using a pin-on-plate tribometer. The results show that, under full lubrication, the adsorbed oil film controlled the friction and wear behavior of steel/steel tribopairs but under starved lubrication, the formation of a tribofilm significantly influenced the tribological behavior. The appropriate textured surfaces with oval-shaped dimples contribute to obtaining excellent antifriction and antiwear behavior. However, excessively high ratios of the major to the minor axis of the oval can result in high contact stresses which can destroy the tribofilm. Highlights: Textured surfaces with oval-shaped dimples were facilely fabricated. Influence of tribofilm formation on the surface tribological behavior was investigated. The adsorbed-film controlled the friction and wear behavior of tribo-pairs under full lubrication. The formation of tribofilm dominated the interface behavior under starved lubrication.